Mechanical and dynamic responses of unidirectional/woven carbon fiber reinforced thermoset and thermoplastic composites after low velocity impact. (5th August 2022) - Kayaaslan, Melihcan; Coskun, Taner; Sahin, Omer Sinan; Unlu, Ulac M; Kadioglu, Ferhat
It is highly important to determine how mechanical and dynamic properties of composite materials will change after impact loads considering the coupled effects of composite design parameters. For these reasons, three-point bending and vibration tests have been carried out for the carbon fiber reinforced thermoset and thermoplastic composites with various stacking sequences before and after low velocity impact, and it is expected that these results achieved from the current study will be beneficial for applications where high damping and impact resistance are demanded together. In this context, vibration tests were carried out under free-free boundary conditions, and their natural frequencies, flexural moduli and structural damping were obtained. Furthermore, three-point tests were conducted in the elastic region with 1 mm/min crosshead speed using a universal test machine, and thus flexural moduli of the composite specimens were obtained. The results were validated by comparing the flexural moduli obtained from the both vibration and three-point bending tests, found to be reliable and comparable. As a result of the current study, it was concluded that woven fabric reinforced composite specimens exhibited 50% higher specific damping capacity (SDC) but 70% lower flexural modulus than unidirectional specimens thanks to biaxially fiber alignment. On the other hand, specific damping capacities of the thermoset and thermoplastic composites with different stacking sequences have been examined, and it was observed that thermoset specimens exhibited unexpectedly 192% higher SDC compared to the thermoplastics. This was interpreted as even though thermoplastics are normally expected to exhibit more damping than thermosets, stacking sequence being more effective on damping responses. Apart from that, although there were slight changes in material properties due to degradation in structural integrity after 2 m/s and 3 m/s low-velocity impacts, it was not found to be significantly effective due to the limited damage areas.